Preoperative Predictors of Soft Tissue Releases Required for Femoral Exposure in Direct Anterior Total Hip Arthroplasty - Michael S. Barnum, MD; Bryan M. Grommersch, MD; Samuel Hovland, BS; George J. Haidukewych, MD; Cody C. Green, MD (Arthroplasty Today)
Background: Sequential soft tissue releases are utilized in direct anterior approach (DAA) total hip arthroplasty (THA) as incomplete femoral exposure may lead to complications. This study identifies patient-specific parameters associated with soft tissue releases required for femoral exposure. Methods: A retrospective review was conducted on 133 patients (150 hips) who underwent primary THA via DAA with a single surgeon. Preoperative radiographic measurements included ilium-ischial ratio (IIR), anterior superior iliac spine to tip of the greater trochanter (AGT), femoral neck-shaft angle (FNA), and articulotrochanteric distance (ATD). Operative reports were reviewed and a multinomial logistic regression model was conducted to identify associations of soft tissue releases. Results: Among patients, 12 (8%) had no release, 94 (62%) had conjoined release, 44 (29%) had conjoined and piriformis releases. Multivariate analysis revealed IIR (OR [odds ratio] 1.68, P = .008), right laterality (OR 7.41, P = .025), and body mass index (BMI) (OR 1.26, P = .041) were associated with conjoined release. BMI (OR 1.51, P = .001), right laterality (OR 7.63, P = .038), and IIR (OR 2.06, P = .001) were also associated with piriformis release. There were no statistically significant differences between AGT, FNA, or ATD between groups. Conclusions: Patients with increased ilium to ischial ratio, right laterality, and larger BMI were associated with greater number of soft tissue releases for adequate femoral exposure. Surgeons may consider these factors to anticipate femoral releases or challenging femoral exposure in direct anterior total hip arthroplasty.